FORMATION OF TEACHERS’ COMPETENCES IN FURTHER EDUCATION - Augskalne, Inese; Garjane, Beatrise (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The interest of contemporary society in improving the quality of education is mainly reflected in the issue of educational results - competences - and their provision in the learning process. Introducing the 21st Century educational standards, the development of competencies required for teaching become more relevant.  International documents indicate that a teacher should have the ability to teach, effectively use technologies in learning, help students gain transversal competencies. The teacher should be able to participate in research, use innovation, reflect on his/her work, collaborate with colleagues and parents. It is the teacher’s duty to direct the student's individual development.Latvian legislation offers wide opportunities for a person employed in education (especially in vocational and education of interests) to become a teacher. It is possible to work as a teacher after attending a short professional development course in education theory. In that case, competences in education (and the right to work at a school) is certified by the B-course certificate after basic training (72 hours total). The goal of this study is to identify and characterize teacher’s competences in education as acquired by teachers during this course. Research methods are a content analysis of 210 questionnaires filled in by vocational education teachers after attending the course and content analysis of their self-assessment.  The results of the research show that teacher’s competences are only partially formed and incomplete. The attitude towards the needs of the student's personality is inappropriate, there is a desire for an authoritarian style.